Preparation, Characterization and Applications of Chitosan-Nanosilica-Graphene Oxide Nanocomposite - Sahila Grace, A.; Prabha Littis Malar, G.S. (Asian Journal of Chemistry, 2021)
In present study, a simple low cost method was used to prepare chitosan-nanosilica-graphene oxide (CS-NSi-GO) nanocomposite. Nanosilica and graphene oxide were synthesized from coconut husk ash and chitosan was synthesized from shrimp shell. Nanosilica was synthesized from coconut husk ash with alkaline extraction using sodium hydroxide followed by precipitation method using sulphuric acid. Graphene oxide was synthesized from the oxidative treatment of the raw material of coconut husk ash. After the synthesis of silica, the carbonized graphite was collected and treated by modified Hummer’s method. The CS-NSi-GO nanocomposite was prepared by condense polymerization method. Various analytical methods such as Fourier transform infrared (FTIR) spectroscopy, Fourier transform Raman (FT-Raman) spectroscopy, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX) and transmission electron microscopy (TEM) were used to characterize the CS-NSi-GO nanocomposite. Eventually antibacterial, antifungal, antioxidant and cytotoxicity of the prepared nanocomposite were also evaluated.